The Analysis of Code Mixing Used By @Dosen_Fashyun Account on Tiktok - Palingga, Helnia Tri; Putri, Kristanti Yuntoro; S, Wawan Herry (Indonesian Research Journal on Education, 2025)
This study discusses about type and factor of code mixing. The purpose of of this thesis to analyze the type of code-mixing that used by @dosen_fashyun account on TikTok. It classifies the code-mixing’s utterances into three types: insertion, alternation, and congruent lexicalization. It also analyzes the factors that motivated @dosen_fashyun account to do code mixing in his explanation in his content video TikTok into two languages, Indonesia and English. This study used qualitative method to analyze the types and factors of code-mixing. The procedures of this research are the data (the transcript of @dosen_fashyun account which arranges by two languages are classified into three types of code-mixing based on Musyken’s theory. Then, the data analyze about the factors which motivated @dosen_fashyun account to do code mixing in his content video on TikTok based on Eunhee Kim’s theory. The result of this research, firstly the types of code-mixing, there were thirty-three sentences include in insertion, and twenty-three sentences include in alternation, and five sentences include in congruent lexicalization. So, congruent lexicalization is dominant in @dosen_fashyun account’s content videos. Secondly, the factors of code-mixing, the researcher did not find the first factor that is participant role and relationship, there were two sentences which include situational factors, two sentences include in message intrinsic factors, and only one sentence is identified as security. So, message intrinsic factor is the dominant factor motivated @dosen_fashyun account to mix his explanation in his content videos.